OP0148 A validation of the 2017 eular/acr idiopathic inflammatory myopathies classification criteria in an expert-defined single-centre ten year incident cohort. (12th June 2018) - Parker, M.J.S; Oldroyd, A.; Roberts, M.E.; Cooper, R.G.; Lilleker, J.B.; Herrick, A.L.; Chinoy, H.
Abstract : Background: The recently published 2017 European League Against Rheumatism (EULAR) and American College of Rheumatology (ACR) classification criteria for adult and juvenile idiopathic inflammatory myopathies (IIM) and their major subgroups reflect a long-appreciated need for more accurate case definition in ongoing research in these complex and heterogenous diseases. 1 However a number of issues remain unresolved. There was a high frequency of missing data in both the derivation and validation samples, only one of the now numerous myositis specific autoantibodies is included, and certain well recognised IIM subtypes are not specifically classified despite their well phenotyped and differing natural histories, clinical features and treatment modalities. 2 3 Objectives: To perform an external validation of the EULAR/ACR classification criteria in an incident IIM cohort and examine how classification criteria-assigned IIM subtype correlates with expert opinion. Methods: Adults with newly diagnosed IIM attending Salford Royal NHS Foundation Trust Neuromuscular services were identified. A retrospective review of all putative cases was performed, and cases fulfilling a consensus expert-opinion diagnosis of definite IIM included. A broad range of clinical, serological and histological data were collected and each case assigned a single IIM subtype by expert opinion. The EULAR/ACR classification criteria were applied and sensitivity, specificity, positive and negative predictive value calculated, presented with 95% confidence intervals (CI). Results: A total of 922 cases were screened with 255 expert opinion definite IIM identified. The sensitivity to diagnose an IIM was 99.6% (97.2–100) and 80.9% (76.0–85.8) for the classification criteria cut-points of 'probable' and 'definite' respectively. The sensitivity for 'definite' IIM improved to 90.2% (86.5–93.8) when biopsy data for 24/34 initially missed cases were excluded. In 94/255 cases the IIM subtype differed between expert opinion and classification criteria, most strikingly in the group subtyped 'polymyositis' using the EULAR/ACR criteria, where there was discrepancy in the majority (87/161). Conclusions: The criteria performed with high sensitivity in identifying IIM in an external cohort of IIM patients. However, substantial disagreement exists in subtype assignment, especially resulting in a larger proportion of cases of 'polymyositis' with heterogeneous features, important to consider in the application of these criteria to subsequent research. References: [1] Lundberg IE, Tjärnlund A, Bottai M, Werth VP, Pilkington C, Visser M De, et al. EULAR/ACR classification criteria for adult and juvenile idiopathic inflammatory myopathies and their major subgroups. Ann Rheum Dis2017;76:1955–64. [2] Betteridge Z, McHugh N. Myositis-specific autoantibodies: An important tool to support diagnosis of myositis. J Intern Med2016;280:8–23. [3] Longo DL, Dalakas MC. Inflammatory muscle diseases. N Engl J Med2015;372:1734–47. Disclosure of Interest: None declared